Comparing the Differential Diagnostic Values of 18F-Alfatide II PET/CT between Tuberculosis and Lung Cancer Patients. (19th February 2018) - Du, Xiaoqing; Zhang, Yu; Chen, Liping; Mi, Baoming; You, Qingjun; Xu, Yuping; Pan, Donghui; Wan, Weixing; Yang, Min; Yu, Chunjing
Abstract : Purpose . To compare the differential diagnostic values of 18 F-Alfatide II PET/CT between tuberculosis and lung cancer patients and in patients with sarcoidosis and common inflammation. Methods . Nine inflammation patients (4 tuberculosis, 3 sarcoidosis, and 2 common inflammation) and 11 lung cancer patients were included in this study. All patients underwent 18 F-FDG and 18 F-Alfatide II PET/CT within 2 weeks, followed by biopsy and surgery. The maximized standard uptake value (SUVmax) and the mean standard uptake value (SUVmean) were evaluated. Results . The active tuberculosis lesions showed a high accumulation of 18 F-FDG, but varying degrees of accumulation of 18 F-Alfatide II, including negative results. The SUVmax of 18 F-Alfatide II in malignant lesions was significantly higher than that in tuberculosis (4.08 ± 1.51 versus 2.63 ± 1.34, P = 0.0078). Three patients with sarcoidosis showed negative results in 18 F-Alfatide II PET/CT. Conclusions . The expression ofα V β 3 is much lower in tuberculosis as compared to that in lung cancer, and accumulation of 18 F-Alfatide II varied even in lesions of the same patient. The negative results of sarcoidosis patients led to the speculation thatα V β 3 was not expressed in those lesions.